MIGA Annual Report 2021 - Multilateral Investment Guarantee Agency (Washington, DC: Multilateral Investment Guarantee Agency, 2021)
In FY21, MIGA issued 5.2 billion US Dollars in new guarantees across 40 projects. These projects are expected to provide 784,000 people with new or improved electricity service, create over 14,000 jobs, generate over 362 million US Dollars in taxes for the host countries, and enable about 1.3 billion US Dollars in loans to businesses—critical as countries around the world work to keep their economies afloat. Of the 40 projects supported during FY21, 85 percent addressed at least one of the strategic priority areas, namely, IDA-eligible countries (lower-income), fragile and conflict affected situations (FCS), and climate finance. As of June 2021, MIGA has also issued 5.6 billion US Dollars of guarantees through our COVID-19 Response Program and anticipate an expansion to 10–12 billion US Dollars over the coming years, a testament to the countercyclical role that MIGA can play in mobilizing private investment in the face of the pandemic. A member of the World Bank Group, MIGA is committed to strong development impact and promoting projects that are economically, environmentally, and socially sustainable. MIGA helps investors mitigate the risks of restrictions on currency conversion and transfer, breach of contract by governments, expropriation, and war and civil disturbance, as well as offering credit enhancement on sovereign obligations.